Repairing the upbringing: Socialization and product repair behavior - Møller, Sophia Rytter; Schmidt, Kamilla Strand-Holm; Laursen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
With growing concerns over sustainability and waste generation both globally and in Denmark, understanding consumer behavior in product repair is crucial. This study investigates in-house product repair behavior in Danish households, focusing on the motivations, and barriers of repairs related to social upbringing. Data was collected as a mixed-methods approach, using 9 qualitative semi-structured interviews as primary data based on secondary picture data collection of self-repaired products from 30 Danes. The study confirms prior studies that show: lack of emotional value, economic feasibility, tools and knowledge as barriers for consumer repairs. Moreover, it contributes by adding multi-socialization during upbringing and types of knowledge, particularly informal repair knowledge from family members, as a crucial determinant in shaping repair behavior specifically related to the knowledge barrier and motivation. This research sheds light on the nuances of Danish household repair behavior, suggesting the integration of repair education in schools and the utilization of repair cafés to foster a sustainable repair culture.